Evaluation of Use of Literature In Language Teaching With Special Reference to Shakespeare’S ‘Hamlet’: Applying Grice's Cooperative Principle to Shakespeare's Hamlet (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Language and Literature are two sides of the same coin.They are inseparable. They are complementary to each other. It is also truethat when somebody has language knowledge and teaches Literature definitely heinfers shades of meaning and enjoys that piece of literature. This researchpaper is an attempt to show how H.P.Grice’s Cooperative Principle particularlyflouting of Conversational Maxims can be applied to Hamlet and how because ofviolation of Conversational Maxims the plot of Hamlet has taken particularshape is shown. This will give a new perspective to the readers of this play.